Stability analysis of steel frames with semirigid connections and semirigid connections with rigidzones - Anh, Vu Quoc (Vietnam Journal of Mechanics, 2001)
To obtain an accurate insight into the behavior of most realistic steel frames, joint flexibility should be allowed for in the analysis since connection flexibility affects both force distribution and deformation in beams and columns of the frames. This paper proposes a method to establish the geometric stiffness matrix and stiffness matrix for semirigid beam element and semirigid beam element with rigidzones. The proposed method can also applied to analyse frame stability with rigid, semirigid and simple connections with rigidzones or without rigidzones. In addition, an approach that evaluates the effective lengthμ factor, thecritical axial load of column in plane frames with rigid, semirigid, and simple connections is also presented.